2018
DOI: 10.3892/mmr.2018.8877
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑146a/Toll‑like receptor 4 signaling protects against severe burn‑induced remote acute lung injury in rats via anti‑inflammation

Abstract: The present study investigated the preventive effects of microRNA (miR)‑146a against severe burn‑induced remote acute lung injury (ALI) in rats and the underlying mechanism. The surface area of the skin was immersed in 100˚C water for 5‑10 sec on the dorsal surface. The expression level of miR‑146a was significantly downregulated in rats with burn‑induced ALI. Downregulation of miR‑146a increased inflammation, and inducible nitric oxide synthase (iNOS) and cyclooxygenase‑2 (COX‑2) expression in a model of ALI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…MicroRNAs (miRNAs) are a class of highly conserved, single-stranded, short noncoding RNAs that suppress the expression of protein-coding genes at the posttranscriptional level [14]. Emerging evidence reveals that miRNAs play a major role in the amelioration of various inflammatory diseases, including ALI [15][16][17]. Recent studies in mouse ALI model showed that miRNA expression profiles are altered after ALI, and modulation of miRNA expression can affect the development of ALI [16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of highly conserved, single-stranded, short noncoding RNAs that suppress the expression of protein-coding genes at the posttranscriptional level [14]. Emerging evidence reveals that miRNAs play a major role in the amelioration of various inflammatory diseases, including ALI [15][16][17]. Recent studies in mouse ALI model showed that miRNA expression profiles are altered after ALI, and modulation of miRNA expression can affect the development of ALI [16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lung IR injury can be alleviated by inhibiting the activation of TLR 2/4 activity (30). Certain studies have shown that miRNA-146a reduces lung injury via the TLR4 / NFκB signaling pathway (31). Similarly, other studies have reported the function of miR-21 in the development of severe primary graft dysfunction by activating the key components of the TLR pathway (27).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-146a-5p is involved in epithelial-fibroblast communication in the lungs, and the pro-inflammatory phenotype of COPD fibroblasts that have been shown to result from dysregulation of epithelial-fibroblast interaction, partly due to the reduced ability of COPD-derived fibroblasts to upregulate miR-146a-5p to counter-regulate pro-inflammatory activity 40 . Furthermore, downregulation of mir-146-a/TLR4 signaling protects against sever burn-induces remote acute lung injury via anit-inflammation 41 . Down-regulation of miR-146a-5p may thus reflect a pro-inflammatory process in grain dust exposed workers.…”
Section: Discussionmentioning
confidence: 99%